Answer :

5x + 9 = 5 + 3x

5x – 3x = 5 - 9

2x = -4

x = -2

L.H.S: 5x + 9
= 5(-2) + 9
= -1

R.H.S: 5 + 3x
= 5 + 3(-2)
= - 1

Since L.H.S. = R.H.S

Hence, the solution is correct.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRD Sharma - Mathematics